1980
DOI: 10.3109/00016348009156933
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Labor by Oxytocin or Prostaglandin E2

Abstract: The efficacy and safety of oral PGE, or intravenous infusion of oxytocin, in both cases combined with early amniotomy, for induction of labor on medical grounds, were compared in a randomized study of 200 women. After an initial dose of 0.5 mg, 1.0 mg of PGE, was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In general the two treatment groups did not differ significantly but nulliparous women were somewhat more common in the prostaglandin group and patients with a low Bishop's score were significantly more frequent in the oxytocin group. The two treatments were equally effective; 91 per cent of the patients delivered vaginally within 24 hours after the start of therapy (10).…”
Section: Amniotomy and Rnrnhgmentioning
confidence: 96%
“…In general the two treatment groups did not differ significantly but nulliparous women were somewhat more common in the prostaglandin group and patients with a low Bishop's score were significantly more frequent in the oxytocin group. The two treatments were equally effective; 91 per cent of the patients delivered vaginally within 24 hours after the start of therapy (10).…”
Section: Amniotomy and Rnrnhgmentioning
confidence: 96%
“…Various investigations carried out over the last 10 years have demonstrated that oral prostaglandin E2 (PGE3 is just as effective as intravenous oxytocin for this purpose (2,5,11,13).…”
mentioning
confidence: 99%